2023
DOI: 10.55951/nurture.v17i2.154
|View full text |Cite
|
Sign up to set email alerts
|

How do students’ digital financial literacy and financial confidence influence their financial behavior and financial well-being?

Abstract: Purpose: An understanding of financial literacy is important not only for business actors but also for individuals and households; even there is a need to introduce this all-important skill to children early. There is a projection that the financial behavior of the young generation will have a better influence on the global economy than that of the previous generation. Therefore, it is crucial that today’s young generation understands financial literacy.   This study aims to measure how digital financial liter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 21 publications
1
10
0
Order By: Relevance
“…The result from the mediation analysis show that financial behaviour mediates the relationship between DFL and FWB, however the mediation role of financial skill on the relationship between DFL and FWB is not statistically supported. The finding of this study appears to be aligned with the findings of some studies that found that DFL has a significant effect on financial behavior, and financial behavior also has a significant effect on FWB (Respati et al, 2023). Another study that share similar results is Setiawan et al (2022), who found that DFL also positively affects the current saving and spending behavior.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…The result from the mediation analysis show that financial behaviour mediates the relationship between DFL and FWB, however the mediation role of financial skill on the relationship between DFL and FWB is not statistically supported. The finding of this study appears to be aligned with the findings of some studies that found that DFL has a significant effect on financial behavior, and financial behavior also has a significant effect on FWB (Respati et al, 2023). Another study that share similar results is Setiawan et al (2022), who found that DFL also positively affects the current saving and spending behavior.…”
Section: Discussionsupporting
confidence: 89%
“…Another study in India found that skills directly affect financial decision-making and perceived financial well-being, and digital financial literacy emerges as a direct and mediating predictor of financial decision-making (Kumar et al, 2023). The mediation effect of financial behavior on the relationship between DFL and FWB is also evident in the literature, confirming the indirect association between the two constructs (Jhonson et al, 2023;Respati et al, 2023). Centered on the discussion mentioned above, this study is conducted with the following two objectives.…”
Section: Introductionmentioning
confidence: 75%
See 2 more Smart Citations
“…This indicates that entrepreneurship education was a flourishing field in the past. The previous educational system frequently helped students build their professional abilities to start their own business strategies [15,16].…”
Section: Entrepreneurship and Entrepreneurship Educationmentioning
confidence: 99%